The applicability of a non-anatomical soft and hard tissue centroid line (S&H centroid) in cephalometrics - Ibrahim S. Al-Shahrani; Khalid M. Al-Balkhi; Abdulaziz Al-Madi (Elsevier, 2010)
The applicability of a newly introduced non-anatomical soft and hard tissue cephalometric centroid line (S&H centroid) was investigated. The "S&H centroid" line established from 12" × 14" lateral cephalometric radiographs of 57 selected adults was used as a base to create a new cephalometric reference line "Centroid-Nasion". The reliability and the use of the newly created "Centroid-Nasion" as a reference line was tested against the conventional "Sella-Nasion" cephalometric reference line to evaluate the sagittal and vertical maxillary and mandibular relationship. Pearson's correlation coefficient, one way ANOVA, and Tukey multiple comparison post Hoc statistical tests were used. The digitization technique was reliable. The "Centroid-Nasion" cephalometric reference line created by utilizing the "S&H centroid" line, was found to be as useful as the conventional "Sella-Nasion" cephalometric plane in establishing and differentiating between sagittal and vertical intermaxillary relationships. Keywords: Non-anatomical, Cephalometric, Centroid, Soft tissue, Hard tissue, Line